Study Study: Mobile application using gamifications for students Who Will do the National High School Exam. - Silva, Samantha Adeline Córdova da; Coelho, Caroline Moraes (INFOCOMP Journal of Computer Science, 2017)
The National High School Examination - ENEM was first applied in 1998. It was created with the objective of evaluating student performance and improving the quality of teaching in the country. Today this exam is one of the main means of access to higher education in the country. Just last year, 9.2 million students took ENEM and this number is increasing more and more, since the goal of the Ministry of Education is that in the near future the ENEM will become the only means of access to higher education in the country, Replacing the vestibular. This article presents a mobile application developed to support teachers and students who prepare for the ENEM, the concepts of gamification, the application will show contents related to the previous exams for the student to study, some questions to test the level of the students with the goal of Offer fun and learning at the same time.